Impact of Cu doping on the structural, morphological and optical activity of V2O5 nanorods for photodiode fabrication and their characteristics. Issue 29 (28th May 2019) - Thangarasu, R.; Babu, B.; Senthil Kumar, N.; Ho, Mon-Shu; Balasundaram, O. N.; Elangovan, T.
Abstract : A wet chemical precipitation method was used to synthesize pure and Cu-doped (3, 5 or 7 at%) V2 O5 nanorods and photodiodes were fabricated. Abstract : In this paper, we report a wet chemical precipitation method used to synthesize pure and Cu-doped V2 O5 nanorods with different doping concentrations (Cu x V2 O5 where x = 3, 5 or 7 at%), followed by annealing at 600 °C and characterizations using several techniques. Indeed, a growth mechanism explaining the morphological evolution under the experimental conditions is also proposed. The XRD patterns revealed that all of the studied samples consist of a single V2 O5 phase and are well crystallized with a preferential orientation towards the (200) direction. The presence of intrinsic defects and internal stresses in the lattice structure of the Cu x V2 O5 samples has been substantiated by detailed analysis of the XRD. Apart from the doping level, there was an assessment of identical tiny peaks attributed to the formation of a secondary phase of CuO. SEM images confirmed the presence of agglomerated particles on the surface; the coverage increased with Cu doping level. XPS spectral analysis showed that Cu in the V 5+ matrix exists mainly in the Cu 2+ state on the surface. The appearance of satellite peaks in the Cu 2p spectra, however, provided definitive evidence for the presence of Cu 2+ ions in these studied samples as well. Doping-induced PL quenching was observed due to the absorption of energy from defect emission in the V 5+ lattice by Cu 2+ ions. We have proposed a cost-effective, less complicated but effective way of synthesizing pure and doped samples in colloidal form, deposited by the nebulizer spray technique on p-Si to establish junction diodes with enhanced optoelectronic properties.